Market Reactions toward Industry 4.0 Technology Investment Announcement: Evidence from Indonesia and the United States - Cheryl Amadea (Universitas Trisakti, 2021)
This study examined market reactions toward announcements of investments in industry 4.0 technology. Market reactions were measured by abnormal returns before and after the announcement date. This study compared the Indonesian and United States of American stock markets through event study methodology using data from 90 announcements of industry 4.0 investments in each country between 2014-2019. The results showed that the American stock market reacted positively towards announcements of industry 4.0 investments, while the Indonesian stock market reacted negatively. Furthermore, based on the industry sector, this study found that industry 4.0 investment announcements in the manufacturing sector for both countries triggered positive market reactions. In comparison, similar investment announcements in the service sector triggered different reactions for the two countries: positive reactions in the US but negative reactions in Indonesia.